2015
DOI: 10.1021/jacs.5b07521
|View full text |Cite
|
Sign up to set email alerts
|

One-step Synthesis of Core-Gold/Shell-Ceria Nanomaterial and Its Catalysis for Highly Selective Semihydrogenation of Alkynes

Abstract: We report a facile synthesis of new core-Au/shell-CeO2 nanoparticles (Au@CeO2) using a redox-coprecipitation method, where the Au nanoparticles and the nanoporous shell of CeO2 are simultaneously formed in one step. The Au@CeO2 catalyst enables the highly selective semihydrogenation of various alkynes at ambient temperature under additive-free conditions. The core-shell structure plays a crucial role in providing the excellent selectivity for alkenes through the selective dissociation of H2 in a heterolytic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
140
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(142 citation statements)
references
References 55 publications
2
140
0
Order By: Relevance
“…[ 21 ] Kinetic experiments showed that the oxidation of alcohol by the active oxygen species at the redox sites of CeO 2 surface was the rate-determining step, and the subsequential condensation with amines can be remarkably promoted by the Lewis sites of CeO 2 ( Figure 48 ) . [ 225 ] The Au@ CeO 2 catalyst provided the highly selective semihydrogenation of various alkynes at ambient temperature without other additives ( Figure 49 f and g). [ 225 ] The Au@ CeO 2 catalyst provided the highly selective semihydrogenation of various alkynes at ambient temperature without other additives ( Figure 49 f and g).…”
Section: Photocatalysts and Organocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 21 ] Kinetic experiments showed that the oxidation of alcohol by the active oxygen species at the redox sites of CeO 2 surface was the rate-determining step, and the subsequential condensation with amines can be remarkably promoted by the Lewis sites of CeO 2 ( Figure 48 ) . [ 225 ] The Au@ CeO 2 catalyst provided the highly selective semihydrogenation of various alkynes at ambient temperature without other additives ( Figure 49 f and g). [ 225 ] The Au@ CeO 2 catalyst provided the highly selective semihydrogenation of various alkynes at ambient temperature without other additives ( Figure 49 f and g).…”
Section: Photocatalysts and Organocatalystsmentioning
confidence: 99%
“…Time course of the hydrogenation of 1a using (f) Au@CeO 2 and (g) Au/CeO 2 .Reproduced with permission [ 225 ]. Elemental mapping images of c) Ce, d) Au, and e) their overlap for Au@CeO 2.…”
mentioning
confidence: 99%
“…The method benefits from the heat generated by LSPR on Au nanoparticles, which induces the polymerization reaction of the ceria precursor sol and results in ceria formation just on the Au nanoparticles surface. Mitsudome et al [108] obtain similar Au/CeO 2 core shell structures by mixing reverse micelle solutions of Au(III), Ce(III), and NaOH. In this mixture, a redox reaction between Au(0) and Ce(IV) occurs yielding the Au/CeO 2 core shell structure.…”
Section: Preparation Of Au/ceo 2 Catalystsmentioning
confidence: 99%
“…For this purpose, various structures, such as core–shell,8, 16, 17, 18, 19, 20, 21 yolk–shell,16, 22 or hollow core–shell,23 were successfully generated, in which noble‐metal NPs were completely encapsulated by the support (e.g., CeO 2 ). However, the concern for such encapsulated structures may fall in the sluggish kinetics of reagents reaching the active catalytic sites, since noble metals like Pt as well as the Pt–CeO 2 interfaces are generally considered as the active sites in many important reactions 4, 24.…”
Section: Introductionmentioning
confidence: 99%